"We Need More Consistency": Negotiating the Division of Labor in ESOL–Mainstream Teacher Collaboration. Issue 1 (17th June 2016) - Peercy, Megan Madigan; Ditter, Margaret; Destefano, Megan
Abstract : This study contributes to research on teacher collaboration, which has not adequately examined the supports and challenges to English for speakers of other languages (ESOL) specialists and mainstream classroom teachers sharing roles in a student‐centered classroom. Using a sociocultural theoretical framework, this study highlights the importance of routine in collaborating teachers' attempts to create a shared division of labor. Using qualitative analysis of interview and observational data, we focus on the division of labor of a coteaching pair, exploring how the teachers used shared teaching goals and tools to facilitate collaboration. Findings indicate that although the teachers valued their collaborative work, interruptions to their routine made it difficult to work productively together at times. This work has implications for administrators and policy makers whose decision making has an impact on teachers' daily schedules. When teachers cannot count on a consistent routine together, they are unable to engage in truly equal coteaching in which both teachers' skills are used to their fullest to benefit not only English language learners, but all students. Future studies should engage in more detailed and sustained observation of coteaching pairs as they negotiate roles and engage in their particular approaches to their division of labor.